Responses of fungal diversity and community composition after 42 years of prescribed fire frequencies in semi-arid savanna rangelands - Poswa, Sanele Briged; Manyevere, Alen; Mashamaite, Chuene Victor (Frontiers in Environmental Science, 2024)
Prescribed fire frequencies have been widely used to reduce the risk of severe wildfire occurrences. In addition, several studies have been conducted to assess the impact of fire frequencies on vegetation, vertebrate, and invertebrate species, as well as soil physical and chemical properties. However, there is a lack of empirically based knowledge concerning the impact of fire frequency on soil microorganisms. This study assessed the effect of different fire frequencies on the diversity and composition of soil fungal communities in a semi-arid savanna rangeland. Soil samples were collected from an ongoing long-term trial at the University of Fort Hare (South Africa) on the following treatments: (i) no burning; (ii) annual burning (burned once every year); (iii) biennial burning (burned once every 2 years); (iv) triennial burning (burned once every 3 years); (v) quadrennial burning (burned once every 4 years); and (vi) sexennial burning (burned once every 6 years). Fungi were identified using high-throughput sequencing, with Shannon-Wiener and Inverse Simpson diversity indexes being used for diversity and network analysis. Principal coordinate analysis was used for Bray-Curtis distance matrices to visualise the relationships between treatments. The highest diversity was found in biennial burning, which was significantly different (p < 0.05) from the sexennial, quadrennial, and no burning treatments but was not different from the triennial and annual burning treatments. Regarding the taxa, Ascomycota and Basidiomycota were the phyla with the highest relative abundance, followed by Mortierellomycota, Chytridiomycota, and Rozellomycota. The different fire frequencies had an influence on soil fungi diversity and taxonomic composition in semi-arid savanna rangelands.